SQL injection strategies : practical techniques to secure old vulnerabilities against modern attacks /: practical techniques to secure old vulnerabilities against modern attacks. (2020) - Galluccio, Ettore; Caselli, Edoardo; Lombari, Gabriele
No abstract available